(untitled) (Bangladesh Journal of Medicine, 2020)
Objective: This study conducted to implement protective measures in healthcare settings during theCOVID-19 pandemic in the context of Bangladesh. Methods: It is an observational survey study. A pre-designed open questionnaire electronic linkusing google form was used to collect data from 500 healthcare workers within Bangladesh in whichparticipants were observed, and variables were measured. Results: The study findings revealed that among all participants, 70.9% were working in COVID-19dedicated hospitals, and 1.8% were diagnosed with COVID-19 while working. The study showed that69.1% of participants washed hands before and after consulting/handling each patient, 69.1% hadreadily available rubs/sanitizer in their healthcare facility, and 65.5% adhered principals ofhandwashing. The study also revealed that only 76.4% of participants maintained aseptic precautionsfor donning/doffing. Conclusion: The study findings recommend that mandatory training and maintaining asepticprecautions for PPE putting on (donning), and removal (doffing) is equally important. Bangladesh J Medicine July 2020; 31(2) :69-75